Australian border policing: regional 'solutions' and neocolonialism. (January 2014) - Grewcock, Michael
Australia's punitive border policing regime, aimed at deterring asylum seekers attempting unauthorised entry into the country, was ratcheted up even further in 2013 by the former Labor-led government and its successor (as of September 2013), the Liberal National Party Coalition. In effect, under the guise of combating 'people-smuggling', and a pledge to 'Stop the Boats', policies such as the mandatory detention of unauthorised arrivals and the use of off-shore detention facilities have been made even more draconian. Now the aim is to block entirely any right to resettlement or residence for refugees in Australia itself, using the weaker and poorer states of Nauru and Papua New Guinea, historically under Australia's control, to act – to their own long-standing detriment – as detention and resettlement centres, for increasing numbers of migrants.